Dexamethasone Resisted Podocyte Injury via Stabilizing TRPC6 Expression and Distribution. (1st April 2012) - Yu, Shengyou; Yu, L.
Abstract : TRPC6, a member of the canonical transient receptor potential channel (TRPC) subfamily, is an important cation selective ion channel on podocytes. Podocytes are highly differentiated cells located on the visceral face of glomerular basement membrane and featured by numerous foot processes, on which nephrin, podocin, and TRPC6 locate. Podocytes and the slit diaphragm (SD) between adjacent foot processes form a selective filtration barrier impermeable to proteins. TRPC6 is very critical for normal podocyte function. To investigate the function of TRPC6 in podocytes and its relation to proteinuria in kidney diseases, we over-expressed TRPC6 in podocytes by puromycin aminonucleoside (PAN) and observed the changes of foot processes, TRPC6 protein distribution, and mRNA expression. Accordingly, in this study, we further investigated the role of specific signaling mechanisms underlying the prosurvival effects of dexamethasone (DEX) on podocyte repair. Our results showed that podocytes processes of overexpressing TRPC6 were reduced remarkably. These changes could be rescued by DEX via blocking TRPC6 channel. Additionally, our results also showed an improvement in TRPC6 arrangement in the cells and decrease of mRNA expression and protein distribution. From these results, we therefore proposed that overexpression of TRPC6 in podocytes may be one of the fundamental changes relating to the dysfunction of the SD and proteinuria. DEX may be maintained the structure and function integrity of SD by blocking TRPC6 signal pathway and played an important role in mechanisms of anti-proteinuria.